Neuropsychiatric symptoms as a distinguishing factor between memory diagnoses. (9th June 2020) - Rouse, Hillary J.; Small, Brent J.; Schinka, John A.; Hazlett, Abigail M.; Loewenstein, David A.; Duara, Ranjan; Potter, Huntington
Abstract : Objectives: To determine whether neuropsychiatric symptoms (NPS) are able to differentiate those with mild cognitive impairment (MCI) and dementia from persons who are cognitively healthy. Methods: Multinomial and binary logistic regressions were used to assess secondary data of a sample (n = 613) of older adults with NPS. Analyses evaluated the ability to differentiate between diagnoses, as well as the influence of these symptoms for individuals with amnestic MCI (MCI‐A), non‐amnestic MCI (MCI‐NA), and dementia compared with those who are cognitively healthy. Results: Persons with MCI were more likely to have anxiety, apathy, and appetite changes compared with cognitively healthy individuals. Persons with dementia were more likely to have aberrant motor behaviors, anxiety, apathy, appetite changes, and delusions compared with those who were cognitively healthy. Individuals with any type of cognitive impairment were more likely to have anxiety, apathy, appetite changes, and delusions. Specifically, anxiety, apathy, appetite changes, and disinhibition were predictors of MCI‐A; agitation and apathy were predictors of MCI‐NA; and aberrant motor behaviors, anxiety, apathy, appetite changes, and delusions were predictors of dementia. Finally, nighttime behavior disorders were less likely in individuals with dementia. Conclusions: The present study's results demonstrate that specific NPS are differentially represented among types of cognitive impairment and establish the predictive value for one of these cognitive impairment diagnoses.